Advancing Brackish Water Aquaculture: Salinity Optimization for Superior Hatching and Survival of Tilapia (Oreochromis niloticus) - Razak, Nurul Fasihah; Thammachot, Nasaporn; Santiag, Cecilia S (Integrated Science Education Journal, 2026)
Purpose of the study: The purpose of this study is to determine the effects of different salinity levels on the hatching success and early survival of Nile tilapia (Oreochromis niloticus) and to identify the optimal salinity range for improving seed quality in brackish-water aquaculture. Methodology: This study used a Completely Randomized Design with four salinity treatments. Incubation utilized fiberglass tanks (100 L), a Milwaukee MA887 refractometer, Hanna HI98107 pH meter, Lutron DO-5509 DO meter, and digital thermometers. Fertile eggs from the Kunti strain broodstock were acclimated and incubated. Data were analyzed using Shapiro–Wilk, Levene, One-Way ANOVA, LSD/Tukey tests in SPSS 26. Main Findings: Shapiro–Wilk and Levene tests confirmed that the data were normal and homogeneous. One-Way ANOVA showed significant effects of salinity on hatching rate and survival. The 10 ppt treatment produced the highest hatchability and larval survival, significantly outperforming the 0,5, and 15 ppt groups. Post-hoc LSD identified 10 ppt as the optimum level. Overall, moderate salinity consistently yielded the best early-performance outcomes for Oreochromis niloticus larvae. Novelty/Originality of this study: This study provides new insights by identifying the optimal salinity range for maximizing hatchability and early larval survival of Oreochromis niloticus using controlled embryonic incubation. Unlike previous works, it integrates precise salinity treatments, standardized hatchery instrumentation, and rigorous statistical testing to define an evidence-based salinity benchmark. The findings advance seed-production strategies for brackish-water aquaculture systems.